Environmental Sanitation in the Coastal Area of Sambuli Village, Nambo District, Kendari City, Southeast Sulawesi Province, Indonesia - Andi Anindyah Artanty; Suryaningsi; Angel Latif (Journal of Health Science and Pharmacy, 2025)
Background: Environmental sanitation is an effort to achieve a healthy environment by controlling physical environmental factors that have adverse impacts on human health and survival. Environmental sanitation plays a vital role in daily life, as it directly affects the health status of individuals and communities. Objective: This study aims to analyze the factors influencing environmental health among coastal communities in Sambuli Village, Nambo District, Kendari City, in 2024. Method: This research employs an analytical observational design with a cross-sectional approach to assess the condition of sanitation and environmental health in the coastal area of Sambuli Village, Nambo District, Kendari City, Southeast Sulawesi Province, Indonesia. Results: The majority of residents in Sambuli Village (66.1%) use drinking water sourced from tap or piped systems, with 92.1% of respondents boiling the water before consumption. Proper toilet ownership, with individual ownership, reached 98.2%. However, all wastewater disposal systems (100%) failed to meet health standards. Furthermore, only 41% of waste disposal sites were covered, and 50% of residents managed household waste by burning it. Conclusion: Environmental sanitation and health conditions in Sambuli Village, Nambo District, Kendari City, Southeast Sulawesi Province, exhibit several positive aspects, such as high toilet ownership and relatively good drinking water treatment practices. Nonetheless, significant challenges remain, particularly in terms of inadequate wastewater disposal systems and improper solid waste management. Thus, infrastructure improvement and community education interventions are essential to enhance environmental sanitation in the area. Keywords: Sanitation, Environment, Drinking Water, Waste, Latrines, Wastewater Disposal System, Sambuli Village